Mental health among people with a migration background in Belgium over the past 20 years: how has the situation evolved? - Camille Duveau; Pierre Smith; Vincent Lorant (BMC, 2023)
Abstract Background Poor mental health is highly stigmatized and stereotyped, even more when it comes to migrant and ethnic minority groups (MEM). Belgium, which has a long history of immigration, is a good case study for analysing how the prevalence of mental illness (MI) has evolved over time and how such evolution had differed between MEM. This paper seeks to explore the prevalence of MI and potential inequalities among MEM compared to native Belgians between 1997 and 2018, shedding light on this important issue. Methods The data set is composed of the six cross-sectional waves of the Belgian Health Interview Survey from 1997 to 2018. The 12-item General Health Questionnaire was used to assess the average level of mental health and the prevalence of MI (score ≥ 4) among five major MEM groups in Belgium (Belgian, Moroccan, Turkish, European migrants, and non-European migrants). Multivariate logistic and linear regression models were used to assess the likelihood of having a MI in the different MEM groups and survey years. The minimal clinically important difference (MID) was also calculated for the severity of MI. Results After controlling for socioeconomic status, the average marginal effect indicated a decrease in mental health among Moroccans and Turks in Belgium between 1997 and 2018, compared to Belgians. This result was confirmed by the Chi²-test, which showed that Turkish (χ²=17.75, p < 0.001) and Moroccans respondents (χ²=4.19, p < 0.04) had a higher overall level of mental distress than Belgians. Furthermore, in 2018, even after adjusting for age, sex and education level, having a mother born in a non-EU country increased the risk of mental illness. Conclusions Mental health inequalities between migrant and ethnic groups are on the rise in Belgium. To address this issue, particular attention should be given to the Moroccan and Turkish background populations. Specific interventions and policies must be implemented to prevent the increase of psychological distress among migrants and ethnic minorities, on the one hand, and ensure that high-quality mental health care is accessible to all, regardless of ethnicity, on the other hand. Additionally, we recommend that future research on ethnic mental healthcare includes better data collection on the country of birth of respondents and their parents.